(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the outpatient morbidity pattern at the Department of Traditional Medicine, Military Hospital 7A, during 2021-2023; identify year-to-year trends; and derive implications for protocol optimization.Subjects and methods: Retrospective cross-sectional study of 19,587 records (January 2021-December 2023). Data were obtained from hospital management software and paper charts; descriptive analysis was performed by ICD-10.Results: Males accounted for 59.6%; working-age patients for 67.2%; 93% resided in Ho Chi Minh city; and 99% had health-insurance coverage. ICD-10 Chapter XIII (Diseases of the musculoskeletal system and connective tissue) comprised 79.73% overall and increased over time (2021: 68.04%; 2022: 77.45%; 2023: 89.65%). The three most frequent diagnoses were cervicobrachial syndrome (M53.1: 31.2%), cervicocranial syndrome (M53.0: 27.7%), and lumbago with sciatica (M54.4: 18.6%). Notable internal-medicine conditions included renal calculus (N20: 2.9%) and chronic sinusitis (J32: 2.3%).Conclusions: Outpatient morbidity at the Department of Traditional Medicine, Military Hospital 7A was dominated by chronic musculoskeletal disorders, with a rising trend in the post-pandemic period. These findings support prioritizing resources, updating the protocol catalogue (neck-shoulder-arm; low back-hip), standardizing integrated traditional medicine with conventional medicine care pathways, and developing diagnosis-group-sp